Seismic response analysis of a new staggered storey isolated structure under mainshock-aftershock sequences - Qianqian Wu; Dewen Liu; Tiange Zhao; Yanping Zheng; Yuan Zhang; Min Lei (Journal of Asian Architecture and Building Engineering, 2024)
Based on a new type of isolated structure, this paper studies the seismic response of the structure under single mainshock and mainshock-aftershock sequences. The new structure developed from the base-isolated structure and the inter-storey isolated structure. To compare its seismic performance with a fixed-base structure, a new staggered storey isolated structure model is developed using ETABS software. The results indicate that during both single mainshock and mainshock-aftershock sequences, the maximum inter-storey displacement of the staggered storey isolated structure is concentrated in the isolated layer, while the stress damage of the core tube mainly occurs between the upper and lower isolated layers. Under mainshock-aftershock sequences, the displacement of the isolated layer is larger than that under the single mainshock, and the distribution of plastic hinges of the frame is greater than that under the single mainshock, compared with the single mainshock sequences, the stress distribution of the core tube and the inter-story displacement of the structure increase by 19.80% anc23%% respectively. Consequently, the damage to the structure under mainshock-aftershock sequences is more severe. The hysteresis curve of the upper isolated layer bearings is more pronounced and demonstrates better energy absorption than that of the lower isolated layer bearings. Overall, the staggered storey isolated structure exhibits better seismic performance than the fixed-base structure. The isolated effectiveness and energy dissipation of the new staggered storey isolated structure improve when the upper isolated layer is lowered.